2019
DOI: 10.1111/are.14402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different carbohydrate levels in puffed feed on digestive tract morphological function and liver tissue structure of snakeheads (Channa argus)

Abstract: The snakeheads are delicate and tender, and it is a high-quality healthcare product with comprehensive nutrition and delicious meat. The snakeheads meat contains up to 16.94% protein; the fat content is only 0.22%, and the protein composition is obviously superior to the vegetable protein, and it is rich in mineral nutrients such as calcium, phosphorus, iron and zinc which are necessary for the human body (Conceição, Dersjant-Li, & Verreth, 1998). Its nourishing medicinal value is also favoured by the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The activities of intestinal antioxidant enzymes, the length of the intestinal villi, and the thickness of the intestinal wrinkled were significantly reduced in Oreochromis niloticus fed a high carbohydrate diet ( Xu, 2017 ). Ding et al (2020) reported that intestinal villi of snakehead ( Channa argus ) became sparse and short as the carbohydrate content of the diet was increased (13–19%), and the intestinal villi were injured and shed at 19% carbohydrate content. In the present study, the intestines of largemouth bass developed moderate to severe necrotizing enteritis with an increase in the number of goblet cells and mucus secretion accompanied by shedding of necrotic epithelial cells and infiltration by inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of intestinal antioxidant enzymes, the length of the intestinal villi, and the thickness of the intestinal wrinkled were significantly reduced in Oreochromis niloticus fed a high carbohydrate diet ( Xu, 2017 ). Ding et al (2020) reported that intestinal villi of snakehead ( Channa argus ) became sparse and short as the carbohydrate content of the diet was increased (13–19%), and the intestinal villi were injured and shed at 19% carbohydrate content. In the present study, the intestines of largemouth bass developed moderate to severe necrotizing enteritis with an increase in the number of goblet cells and mucus secretion accompanied by shedding of necrotic epithelial cells and infiltration by inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that dietary energy source (corn starch and lipid) and additives (brewer's yeast and sanguinarine) levels had considerable effects on intestinal microbial relative abundance in phylum level. (Arias-Jayo et al, 2018;Ding et al, 2020;Zhang et al, 2019;Zhou et al, 2018). So, we speculated that the relative abundance of intestinal microbe was considerably affected by the dietary starch level in phylum level.…”
Section: High-starch Diet Impaired Intestinal Microbial Barriermentioning
confidence: 99%
“…As is known, starch is one of the most important energy sources of carbohydrate and binder in commercial aquafeed. A moderate amount of dietary carbohydrates could reduce production costs in sh, via increase protein deposition, growth, feed e ciency in sh, such as pompano (Trachinotus ovatus), snakehead (Channa argus) and rainbow trout (Oncorhynchus mykiss) (Castro et al, 2015;Ding et al, 2020;KROGDAHL et al, 2005). As a carnivorous sh, the largemouth bass has limited capacity to utilize starch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, exogenous digestive enzymes can also help aquatic animals to decompose some anti-nutrients, improve the digestibility and utilization of feed, and promote animal growth [7,8]. Our previous studies have shown that snakeheads fed a combination with conventional feeds may have damaged and deficient villi due to incomplete feed absorption [9]. However, the supplementation of amylase to snakehead feed was thought to promote starch utilization and alleviate barriers to carbohydrate consumption [10].…”
Section: Introductionmentioning
confidence: 99%